Saturated Interference in SAR: Theoretical Analysis and Suppression Solutions - Lunhao Duan; Xingyu Lu; Jianchao Yang; Huizhang Yang; Shiyuan Zhang; Guanqi Tong; Ke Tan; Zheng Dai; Hong Gu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Synthetic aperture radar (SAR) systems are highly sensitive to interference, making interference suppression a critical concern. While significant research has been conducted on SAR interference suppression using parametric, nonparametric, semiparametric methods, and machine learning, these studies often neglect the impact of high-power interference, which can saturate SAR receivers due to their limited dynamic range. This saturation can lead to the model mismatch and performance degradation of many previously studied suppression methods. In this article, we provide a detailed analysis of saturated interference in SAR systems. We develop time-domain saturation signal models for different types of interference, and analyze the frequency domain spurious characteristics of saturated interference. Based on this analysis, we propose novel interference suppression method adapted for saturated narrowband and wideband interference. We validate our methods using semiactual data from Radarsat-1, demonstrating their effectiveness in suppressing both narrowband and wideband saturated interference. Besides, we also conducted analysis and verification using the real saturated interference data of Gaofen-3. The results confirm the proposed methods' capability to enhance SAR performance under saturation conditions.